Co-evolution of platform architecture, platform services, and platform governance : Expanding the platform value of industrial digital platforms - Jovanovic, Marin; Sjödin, David; Parida, Vinit (Elsevier, 2021)
Industrial manufacturers increasingly develop digital platforms in the business-to-business (B2B) context. This emergent form of digital platforms requires a profound yet little understood holistic perspective that encompasses the co-evolution of platform architecture, platform services, and platform governance. To address this research gap, our study examines multiple platform sponsors from an industrial manufacturing context. The study demarcates three platform archetypes: product platform, supply chain platform, and platform ecosystem. We argue that each platform archetype involves a gradual development of platform architecture, platform services, and platform governance, which mirror each other. We also find that each platform archetype is characterized by a specific innovation mechanism that contributes to the platform service discovery and expands the platform value. Our study extends the co-evolution perspective of platform ecosystem literature and digital servitization literature.
Keywords: Digital servitization; Industrial digital platforms; Platform architecture; Platform service; Platform ecosystem; fi=Strateginen johtaminen|en=Strategic Management|